2019
DOI: 10.1021/acsmedchemlett.8b00495
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cyclic Biphalin Analogues by Ruthenium-Catalyzed Ring Closing Metathesis: in Vivo and in Vitro Biological Profile

Abstract: In this work we report the application of the ring-closing metathesis (RCM) to the preparation of two cyclic olefin-bridged analogues of biphalin (Tyr-D-Ala-Gly-Phe-NH-NH ← Phe ← Gly ← D-Ala ← Tyr), using the second generation Grubbs' catalyst. The resulting cis-and trans-cyclic isomers were identified, fully characterized, and tested in vitro at μ (ΜΟR), δ (DOR), and κ (KOR) opioid receptors and in vivo for antinociceptive activity. Both were shown to be full agonists at MOR and potential partial antagonists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…We next measured the functional activity of all compounds at the opioid receptors using the same CHO cell lines used above for the binding. We used 35 S-GTPγS coupling, which we’ve used extensively to characterize the functional activity of our compounds. , …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We next measured the functional activity of all compounds at the opioid receptors using the same CHO cell lines used above for the binding. We used 35 S-GTPγS coupling, which we’ve used extensively to characterize the functional activity of our compounds. , …”
Section: Resultssupporting
confidence: 90%
“…We used 35 S-GTPγS coupling, which we've used extensively to characterize the functional activity of our compounds. 20,25 We first found that all 3 compounds were partial agonists at the DOR (E MAX 47−62%), with modest potencies (EC 50 40− 250 nM, Figure 2). These potencies were all about 2-fold worse than the binding affinities measured in Figure 1, suggesting that these ligands have somewhat poor intrinsic efficacy at the DOR.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This peptide then served as a scaffold for the creation of numerous cyclized and linear derivatives, mainly headed by Adriano Mollica's research group. These daughter compounds also showed potent anti-nociception and, in some cases, reduced side effect liability (e.g., Stefanucci et al, 2019).…”
Section: μ Receptor /δ Receptor Dual Agonistsmentioning
confidence: 99%
“…The peptidomimetic analogs, generated by modifying the parent compounds, are initially assessed through in vitro methods such as radio-receptor and cAMP assays and eventually tested for in vivo activity. Analogs that do not display a remarkable difference in potency as compared to the parent or template molecule through in vitro studies may prove to be significantly more potent based on in vivo analysis (Stefanucci et al, 2019).…”
Section: Introductionmentioning
confidence: 99%